Economic Appraisal for Multiregional Impacts by a Large-scale Expressway Project - Toshihiko Miyagi (Tinbergen Institute, 2001)
The paper describes the development of a spatial computable general equilibrium(SCGE) model aimed atestimating the indirect economic effects arising from a large scale of transportproject (Tokai-HokurikuExpressway) in the Chubu (meaning central) region in Japan. We have adopted ajoint parameter estimation ofcalibration technique, statistical estimation and literature quotation forestimating the Japanese inter-regionalaccount consisting of nine major regions with the national account being thebenchmark equilibrium data. We haveobtained highly compatible estimates with the surveyed interregional accounts inthe application of the SCGEmodel. Modal split function in freight transport is also developed which can beimportant factor in the evaluation ofeconomic effects in transport projects.The paper reports that economic effects of the project extended over wholecountry through the so-calledmultiplier effects of the economy, which could not be measured by thetraditional method.
Keywords: 330; Verkehrspolitik; Autobahn; Regionale Inzidenz; Räumliche Gleichgewichtstheorie; Allgemeines Gleichgewicht; Theorie; Japan